Frameworks of IT prosumption for business development - Pankowska, Magorzata (Business Science Reference, 2014)
"This book investigates the latest empirical research on active use of information technology resources, enabling users with new methodologies, tools, and opportunities to impact application development processes"--Provided by publisher
Keywords: Business enterprises -- Technological innovations; Decision support systems